The Kyrgyz Republic : Fifth Review Under the Three-Year Arrangement Under the Extended Credit Facility, and Request for Modification of Performance Criteria. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2013)
This paper focuses on the Kyrgyz Republic's Fifth Review Under the Three-Year Arrangement Under the Extended Credit Facility, and Request for Modification of Performance Criteria. Growth was strong over the first nine months of 2013, and inflation has declined steadily. Intensive public investment programs and the decline in gold prices are putting temporary pressures on the current account. The medium-term outlook is broadly favorable, despite the slowdown in the region. System-wide financial stability indicators have been broadly sound. The IMF staff recommends completion of the fifth review and approval of the request for modification of the performance criteria for end-December 2013.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet